2013
DOI: 10.1590/0037-8682-0098-2013
|View full text |Cite
|
Sign up to set email alerts
|

Possible artemisinin-based combination therapy-resistant malaria in Nigeria: a report of three cases

Abstract: Artemisinin-based combination therapy-resistant malaria is rare in Sub-Saharan Africa. The World Health Organization identifi es monitoring and surveillance using day-3 parasitaemia post-treatment as the standard test for identifying suspected artemisinin resistance. We report three cases of early treatment failure due to possible artemisinin-based combination therapy-resistant Plasmodium falciparum malaria. All cases showed adequate clinical and parasitological responses to quinine. This study reveals a need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…The absence of ETF and low recurrent malaria (only 1 LCF) in the present study could imply high therapeutic efficacy of both components of AL in the study site. Studies in Ethiopia [23] and Nigeria [40] reported two and three ETF cases of AL treatment respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of ETF and low recurrent malaria (only 1 LCF) in the present study could imply high therapeutic efficacy of both components of AL in the study site. Studies in Ethiopia [23] and Nigeria [40] reported two and three ETF cases of AL treatment respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that about 9% of the Ghanaian population use HPs for malaria treatment [3]. With the looming possibility of parasite resistance to the recommended ACT [14] coupled with difficulties in affordability and accessibility to these drugs in remote and poor areas in the country, anti-malarial herbal preparations would continue to be an important and sustainable source of malaria treatment in Ghana. It must however be emphasized that the use of these preparations must be closely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Although ACT-resistant malaria is rare in Africa, there is a historical precedence of resistance to antimalarial medicine emerging in Asia and spreading to Africa [26]. Three cases of early treatment failure due to possible ACT-resistant P. falciparum malaria have been reported in Nigeria [27]. There has also been a case of possible artemether-lumefantrine treatment failure in an Italian traveler with uncomplicated P. falciparum malaria imported from the Democratic Republic of the Congo [28].…”
Section: Discussionmentioning
confidence: 99%